The pale king : an unfinished novel - Wallace, David Foster (Hamish Hamilton, 2011)
The character David Foster Wallace is introduced to the banal world of the IRS Regional Examination Center in Peoria, Illinois, and the host of strange people who work there, in a novel that was unfinished at the time of the author?s death